Pembinaan Renang Barracuda’s Swimming Club di Kota Malang - Presila Dwiky Alvionita; Roesdiyanto Roesdiyanto (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The purpose of this service is to find out about Barracuda's Swimming Club swimming coaching in order to support athlete achievement. The context of this service is coaching the Barracuda's Swimming Club swimming to produce outstanding athletes. The subject is the Barracuda's Swimming Club pre-achievement athlete. The data collection technique is direct observation technique. The method used is a qualitative method. The results and discussion of this service were obtained from the development of Barrcuda's Swimming Club pre-achieved swimming athletes, namely the introduction of basic swimming techniques which are the first step for swimming, instilling a tough spirit in competing as a provision to face competition, and providing motivation is the coach's job to encourage enthusiasm for training.